Pengaruh Literasi Keuangan dan Sikap Keuangan terhadap Kesejahteraan Keuangan dengan Perilaku Keuangan sebagai Variabel Mediasi: Studi pada Pegawai Negeri Sipil di Provinsi Jambi - Ario Gusmansyah; Tona Aurora Lubis; Agus Solikhin (Management Department, Faculty of Economics and Business, Universitas Jambi, 2025)
This study aims to analyze the influence of financial literacy and financial attitude on financial well-being, with financial behavior as a mediating variable among civil servants at the Regional Financial and Revenue Management Agency (BPKPD) of Jambi Province. Using a quantitative approach with Structural Equation Modeling (SEM-PLS), data were collected from 175 respondents through structured questionnaires. The results indicate that financial behavior is the strongest and most dominant predictor in determining financial well-being. Interestingly, the findings reveal that financial literacy has no direct effect on financial behavior, indicating a knowledge-behavior gap among the officers. However, financial attitude is proven to be the primary driver in shaping disciplined financial behavior. The mediation test confirms that financial behavior acts as a crucial bridge that transforms knowledge and attitude into tangible financial well-being. This study recommends that government agencies focus on educational programs based on behavioral and mental shifts, rather than merely providing theoretical materials.